(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
Good public administration requires capable workers. This has always been true, but its importance to the local community has probably never been more important than it is today. The function of human resources management is to provide the employees development of their capability through management system from selection and recruitment to promotion and advancement, benefits, compensation, career development, etc. The function, in terms of the employer’s benefit, is to create a management system to achieve long-term goals and plans. The management allows organizations to study, target, and execute long-term employment goals. As well as any real company, the goal of public administration human resource management to have an efficient ability to grow and advance human resource management is a key. New objectives of human resources (hereinafter – HR) services include the effective implementation of HR policy and coordination of HR management in a government (national and local) organization. Therefore, the responsibilities of HR management and system are starting to embrace a wider range of activities, including the development of labor motivation systems, management of professional promotion, and diagnostic method of auditing in HR management in a public administration. Enhancing efficiency of public administration management, quality of public services they deliver, and implementation of state functions have become the key focus of all broad reforms in the civil service in the Republic of Macedonia.